On IoT Security Models:Traditional and Block chain - Haq, Shahid Ul; Singh, Yashwant (International Journal of Computer Sciences and Engineering, 2025)
Security and privacy is a much-needed aspect of the connected world. If these functionalities are not deployed properly then every economic or societal institution dependent on them are vulnerable to get crashed and might even cause a damage of catastrophic scale. People would eventually stop trusting these technological platforms that are supposed to make their lives better. Although security is a paramount functionality in any connected infrastructure, there is no silver bullet to it, there has been extensive research in this field but no one has come up with an idea that can secure the distributed and heterogeneous IoT network efficiently. IoT demands an autonomous access control methodology requiring minimal or no user interaction. There are several existing models that are good and effective however they have several implementation issues. In this paper we have described our survey of the existing security models of IoT and presented a brief comparative analysis of the discussed models also some of the main requirements for designing such models is given.